Satisfaction and Usefulness of Virtual Learning Environment Platform as a Basis for Continous Utilization - Calpo, Valentin B. (International Journal of Psychosocial Rehabilitation, 2020)
The study was conducted to assess the level of satisfaction and usefulness of virtual environment platform (Google Classroom) among PSU-OUS doctoral and master students of Lingayen and Alaminos centers as an alternative instructional delivery tool and if these are related to their profile variables. The study made use of the descriptive-correlational methods of research with the survey type of questionnaire utilizing Google Forms. The participants of the study were chosen through purposive sampling and were limited to the masteral and doctoral students of the PSU-OUS, who are currently enrolled in the Doctor of Education, MA Education majors in Educational Management and Instructional Leadership, and Master in Development Management major in Public Management programs SY 2016-2018, and who underwent the Google classroom online courses. The PSU-OUS student-respondents were mostly female, aged 31-50 years old, married, and are mostly Teachers I-III. Google Classroom is very useful along with academic and non-academic activities, and professional development to the student-respondents. The student-respondents are very satisfied in the use of Google Classroom as an Instructional Delivery Platform in terms of its usability or functionality, provision of quality information, and professor's interaction. There is a moderate to a significant relationship between the student-respondents' level of satisfaction in terms of its usability/functionality and provision of quality information, professors' interaction and their profile variables.